ZONING OF AREAS WITH SUSCEPTIBILITY TO OAK DECLINE IN WESTERN IRAN - Ghanbari Motlagh, Mohadeseh; Kiadaliri, Masoud (Quaestiones Geographicae, 2021)
Zagros forests have the greatest impact on soil and water protection in western Iran. Despite this, a significant part of these forests, especially in Ilam province, have suffered a lot due to the phenomenon of oak decline. The first and most fundamental thing a person must know when combating this issue is the distribution of these areas in forests. Therefore, using the parameters affecting the decline in the forests of Ilam province and based on fuzzy logic, a map of susceptible to oak decline areas was prepared. In this study, the parameters of temperature and precipitation, slope, aspect, altitude, distance from farmlands, roads and forest density were selected as effective parameters and fuzzy gamma overlap method was used. The results showed that more than 77% of the oak forests in the province are highly and extremely susceptible to the decline. This confirms the need for rapid action to plan and protect these forests. In addition, the fuzzy method is proposed, which is considered as a fast and efficient method in preparing such maps for other areas